Integrated physiological and transcriptomic analyses reveal the molecular mechanism behind the response to cultivation in Quercus mongolica - Jiang, Min; Li, Xinman; Yuan, Yangchen; Zhang, Guowei; Pang, Jiushuai; Ren, Junjie; Wang, Jinmao; Yang, Minsheng (Frontiers in Plant Science, 2022)
Quercus mongolica, a common tree species for building and landscaping in northern China, has great commercial and ecological value. The seedlings of Q. mongolica grow poorly and develop chlorosis when introduced from high-altitude mountains to low-altitude plains. Effective cultivation measures are key to improving the quality of seedlings. To investigate the complex responses of Q. mongolica to different cultivation measures, we compared the adaptability of 3-year-old Q. mongolica seedlings to pruning (P), irrigation (W), and fertilization (F [nitro compound fertilizer with 16N-16P-16K]). Physiological measurements and transcriptome sequencing were performed on leaves collected under the P treatments (control, cutting, removal of all lateral branches, and removal of base branches to one third of seedling height), the W treatments (0, 1, 2, 3, 4, or 5 times in sequence), and the F treatments (0, 2, 4, and 6 g/plant). Analyses of the physiological data showed that P was more effective than W or F for activating intracellular antioxidant systems. By contrast, W and F were more beneficial than P for inducing the accumulation of soluble sugar. OPLS-DA identified superoxide dismutase, malondialdehyde, and peroxidase as critical physiological indices for the three cultivation measures. Transcriptome analyses revealed 1,012 differentially expressed genes (DEGs) in the P treatment, 1,035 DEGs in the W treatment, and 1,175 DEGs in the F treatment; these DEGs were mainly enriched in Gene Ontology terms related to the stress response and signal transduction. Weighted gene coexpression network analyses indicated that specific gene modules were significantly correlated with MDA (one module) and soluble sugar (four modules). Functional annotation of the hub genes differentially expressed in MDA and soluble sugar–related modules revealed that Q. mongolica responded and adapted to different cultivation measures by altering signal transduction, hormone levels, reactive oxygen species, metabolism, and transcription factors. The hub genes HOP3, CIPK11, WRKY22, and BHLH35 in the coexpression networks may played a central role in responses to the cultivation practices. These results reveal the mechanism behind the response of Q. mongolica to different cultivation measures at the physiological and molecular levels and provide insight into the response of plants to cultivation measures.